Pengaruh Brand Image, Brand Awareness, Brand Trust Dan Product Knowledge Terhadap Minat Pembelian Pada Fesyen Busana Muslim Khayrscarf Di Kota Malang - Callista, Arwa Diba Ratu; Arifin, Rois (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to determine the influence of brand image, brand awareness, brand trust and product knowledge on purchasing interest in Khayrscarf Muslim fashion fashion in Malang City. The sampling technique used purposive sampling to obtain a sample of 80 respondents. The data collection method uses a questionnaire. The data analysis technique used in this research is multiple linear regression. The research results show that simultaneously Brand Image, Brand Awareness, Brand Trust and Product Knowledge have a positive and significant effect on purchasing interest. Likewise, partially Brand Image, Brand Awareness, Brand Trust and Product Knowledge have a positive and significant effect on purchasing interest. Keywords: Brand Image, Brand Awareness, Brand Trust, Product Knowledge, Purchase Interest